Sentinel node mapping in thyroid cancer: an overview - Puccini, Marco; Ambrosini, Carlo Enrico; Rossi, Leonardo; De Napoli, Luigi; Materazzi, Gabriele (Frontiers in Medicine, 2023)
In this perspective article we look at the current status of sentinel node mapping (SNM) in thyroid tumors and to its potential perspectives. SNM in thyroid cancer has been tested since the end of ‘900, mainly in papillary thyroid cancer (PTC), but also in medullary thyroid cancer (MTC). In PTC it has been employed to find occult lymph node metastases in the central compartment of the neck as an alternative or an indication to prophylactic dissection, by the means of several methods. All of them has proven effective in spotting sentinel nodes, but the results have been somewhat lessened by the uncertainty about the clinical significance of occult metastases in differentiated thyroid cancer. SNM in MTC has been used to find occult lymph node metastases in the lateral compartments of the neck, here too with excellent results hindered by a similar doubt about the real clinical significance of MTC micrometastases. Well designed, adequately sized RCT are lacking, so SNM in thyroid tumors remains an interesting but yet experimental methodology. New technology is emerging that could ease the project of such studies, which could add solid informations about the clinical significance of occult neck metastases in thyroid cancer.